Four-Year Outcomes of Two Second-Generation Trabecular Micro-Bypass Stents in Patients with Open-Angle Glaucoma on One Medication - Lindstrom R (Dove Medical Press, 2020)
Richard Lindstrom, 1 Steven R Sarkisian, 2 Richard Lewis, 3 John Hovanesian, 4 Lilit Voskanyan 5 1Minnesota Eye Consultants, Minneapolis, MN, USA; 2Oklahoma Eye Surgeons, PLLC, Oklahoma City, OK, USA; 3Sacramento Eye Consultants, Sacramento, CA, USA; 4Harvard Eye Associates, Laguna Hills, CA, USA; 5S.V. Malayan Ophthalmology Centre, Glaucoma Department, Yerevan, ArmeniaCorrespondence: Richard LindstromMinnesota Eye Consultants, 710 E 24th St, Suite 100, Minneapolis, MN 55404, USATel +1 612-813-3600Fax +1 952-567-6156Email rllindstrom@mneye.comIntroduction: This study evaluated long-term reductions in intraocular pressure (IOP) and medication following implantation of 2 second-generation trabecular micro-bypass stents (iStent inject®) in eyes with open-angle glaucoma (OAG) not controlled on 1 preoperative medication.Material and Methods: In this prospective interventional multi-surgeon study, standalone implantation of 2 iStent inject stents was performed in 57 eyes of 57 subjects with OAG, preoperative IOP of 18– 30 mmHg on 1 medication, and preoperative post-washout IOP of 22– 38 mmHg. The main outcome measures included the proportions of eyes achieving medication-free IOP ≤ 18 mmHg, IOP ≤ 15 mmHg, or ≥ 20% IOP reduction versus preoperative unmedicated IOP. Assessments included IOP, medications, visual acuity, visual field, pachymetry, complications, and interventions. Subjects were followed for 48 months with follow-up continuing in all eyes.Results: At Month 48 (n=57), 95% of eyes achieved an IOP reduction of ≥ 20% without medication versus preoperative washout IOP; and although they had eliminated medication, 81% of eyes still had an IOP reduction of ≥ 20% versus preoperative IOP on 1 medication. Mean 48-month unmedicated IOP decreased by 46% to 13.2± 1.6 mmHg vs 24.4± 1.3 mmHg preoperatively (p< 0.0001), with 95% of medication-free eyes having IOP ≤ 18mmHg and 82% having IOP ≤ 15mmHg. Over the course of follow-up, 3 eyes had medication added and 1 eye underwent a secondary glaucoma surgery, and safety parameters were favorable.Discussion: Standalone iStent inject implantation in OAG patients on 1 preoperative medication resulted in average IOP reduction to ≤ 15 mmHg with the elimination of medication and favorable safety through 48 months.Trial Registration: ClinicalTrials.gov identifier, NCT02868190.Keywords: glaucoma, MIGS, trabecular micro-bypass, second-generation, prostaglandin, iStent inject